The determinants and consequences of FDI: evidence from Chinese manufacturing firms - Wang, Hao (2014)
Using a very comprehensive Chinese firm-level data covering the period of 2000 to 2005, this thesis empirically assesses the determinants and consequences of Foreign Direct Investment (FDI) in China. In particular, the novelty of this research lies in our firm-level analysis which is based on a large sample of firms in 31 host provinces, allowing us to explore the question by distinguishing different modes of FDI inflows.